2020
DOI: 10.32910/ep.71.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Panel Granger causality analysis of relationships between tourism and economic growth in the top eight tourist destinations

Abstract: The tourism has economic, social and political effects and contributes to the economic development of many countries. Interaction levels of national economies increase with tourism through globalization. This study aims to test the causality relationship between the components of the tourism and economic growth. The causality relationship between the components of the tourism and economic growth by using panel causality analysis method. The findings indicate a bi-directional causality relationship between grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As illustrated in Table 1, tourist arrivals, tourism expenditures, and tourism receipts are mainly used as proxy measures of tourism (Soylu, 2020; Antonakakis et al, 2019; Risso, 2018). These volume-based variables are theoretically sound, but their use in analyses may yield different results (Can and Gozgor, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Table 1, tourist arrivals, tourism expenditures, and tourism receipts are mainly used as proxy measures of tourism (Soylu, 2020; Antonakakis et al, 2019; Risso, 2018). These volume-based variables are theoretically sound, but their use in analyses may yield different results (Can and Gozgor, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several academic studies conducted by , , Liu et al (2021), Soylu (2020), Khan (2020a and b), Wang (2012), Simatupang (2018), andJaforullah (2015) have consistently found that tourism has a positive impact on economic development. This underscores the significance of regulators, legislators, investors, organizations, and other societal stakeholders diligently overseeing and addressing these emissions.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Since then, researchers have only looked at the growing concerns regarding the factors responsible for greenhouse gas emissions; among them, the travel industry is one of them. In connection with this, several researchers, like Liu et al [6], Soylu [7], Wang [8], Simatupang [9], and Jaforullah [10], and who studied the tourism-growth nexus, found that tourism boosts economic growth. In connection with this, Lanza and Pigliaru [11] were some of the first to look at the relationship between tourism and growth from a theoretical point of view.…”
Section: Literature Reviewmentioning
confidence: 97%